The Role of Digital Technology in Enhancing Blue Economy Sustainability: Advancing Global Fisheries Management through Innovation and Governance - Candido, Antonio; Goncalves, Goncalves (Cebong Journal, 2025)
The Role of Digital Technology in Enhancing Blue Economy Sustainability: Advancing Global Fisheries Management through Innovation and Governance This study examines the role of digital technology in promoting the sustainability of global fisheries within the framework of the blue economy. Traditional approaches to fisheries management often face limitations in data accuracy, traceability, and enforcement, resulting in overfishing and ecosystem degradation. The primary objective of this research is to analyze how digital technologies contribute to enhancing the sustainability of global fisheries within the framework of the blue economy, while also identifying challenges, policy implications, and best practices. The study adopts a qualitative descriptive research design using a literature-based approach. It synthesizes findings from peer-reviewed journals, policy reports, and global case studies to assess the application of digital technologies such as blockchain, artificial intelligence (AI), Internet of Things (IoT), and satellite monitoring in fisheries management. Comparative analysis between traditional practices and digital solutions was conducted to evaluate improvements in efficiency, traceability, and ecological outcomes. The findings show that digital technology enhances fisheries management by enabling real-time monitoring, improving supply chain transparency, reducing illegal, unreported, and unregulated (IUU) fishing, and supporting small-scale fishers through data-driven decision-making. Compared to traditional practices, digital tools provide more reliable, adaptive, and scalable solutions to address overfishing and marine ecosystem degradation. However, barriers such as limited infrastructure, high implementation costs, digital literacy gaps, and governance challenges restrict widespread adoption. This research concludes that digital technology significantly improves sustainability outcomes in fisheries when integrated with supportive policies, international cooperation, and private sector engagement. To maximize impact, multi-stakeholder collaboration and investments in capacity building are essential, particularly in developing regions.